iTRAQ-based proteomic analysis of the reproductive cycle characteristics of Hainan Black Goat, the unique species in China, Hainan Province - Wu, Kebang (Emirates Journal of Food and Agriculture, 2018)
Hainan black goats are unique species in China, Hainan province, they are specific mutton goat breed and the tasty meat make the black goat to be one of the four famous dishes in Hainan. However, little knowledge was known about the reproductive cycle of this breed. So, in the study, serum samples of the reproductive period were collected, and high-throughput sequencing were conducted by iTRAQ technology. The results showed the amounts of significantly different proteins between continuous period and the corresponding Go and COG annotation, KEGG enrichment of differential expressed proteins between each two periods were also analyzed. Further, continuously differential expression proteins of the whole cycle and differential expression proteins directly related to reproduction between two adjacent periods were also collected and annotated. This is the first study systematically uncovered reproductive cycle characteristics of Hainan black goats, the study preliminarily uncovered the basical protein information between each reproductive period, and the data could contribute to the built of highly efficient reproduction system of Hainan black goats.